<< Chapter < Page Chapter >> Page >

We eliminate one variable using row operations and solve for the other. Say that we wish to solve for x . If equation (2) is multiplied by the opposite of the coefficient of y in equation (1), equation (1) is multiplied by the coefficient of y in equation (2), and we add the two equations, the variable y will be eliminated.

b 2 a 1 x + b 2 b 1 y = b 2 c 1 Multiply  R 1  by  b 2 b 1 a 2 x b 1 b 2 y = b 1 c 2 Multiply  R 2  by b 1 ________________________________________________________   b 2 a 1 x b 1 a 2 x = b 2 c 1 b 1 c 2

Now, solve for x .

b 2 a 1 x b 1 a 2 x = b 2 c 1 b 1 c 2 x ( b 2 a 1 b 1 a 2 ) = b 2 c 1 b 1 c 2                         x = b 2 c 1 b 1 c 2 b 2 a 1 b 1 a 2 = [ c 1 b 1 c 2 b 2 ] [ a 1 b 1 a 2 b 2 ]

Similarly, to solve for y , we will eliminate x .

a 2 a 1 x + a 2 b 1 y = a 2 c 1 Multiply  R 1  by  a 2 a 1 a 2 x a 1 b 2 y = a 1 c 2 Multiply  R 2  by a 1 ________________________________________________________ a 2 b 1 y a 1 b 2 y = a 2 c 1 a 1 c 2

Solving for y gives

a 2 b 1 y a 1 b 2 y = a 2 c 1 a 1 c 2 y ( a 2 b 1 a 1 b 2 ) = a 2 c 1 a 1 c 2                          y = a 2 c 1 a 1 c 2 a 2 b 1 a 1 b 2 = a 1 c 2 a 2 c 1 a 1 b 2 a 2 b 1 = | a 1 c 1 a 2 c 2 | | a 1 b 1 a 2 b 2 |

Notice that the denominator for both x and y is the determinant of the coefficient matrix.

We can use these formulas to solve for x and y , but Cramer’s Rule also introduces new notation:

  • D : determinant of the coefficient matrix
  • D x : determinant of the numerator in the solution of x
    x = D x D
  • D y : determinant of the numerator in the solution of y
    y = D y D

The key to Cramer’s Rule is replacing the variable column of interest with the constant column and calculating the determinants. We can then express x and y as a quotient of two determinants.

Cramer’s rule for 2×2 systems

Cramer’s Rule    is a method that uses determinants to solve systems of equations that have the same number of equations as variables.

Consider a system of two linear equations in two variables.

a 1 x + b 1 y = c 1 a 2 x + b 2 y = c 2

The solution using Cramer’s Rule is given as

x = D x D = | c 1 b 1 c 2 b 2 | | a 1 b 1 a 2 b 2 | , D 0 ; y = D y D = | a 1 c 1 a 2 c 2 | | a 1 b 1 a 2 b 2 | , D 0.

If we are solving for x , the x column is replaced with the constant column. If we are solving for y , the y column is replaced with the constant column.

Using cramer’s rule to solve a 2 × 2 system

Solve the following 2   ×   2 system using Cramer’s Rule.

12 x + 3 y = 15    2 x 3 y = 13

Solve for x .

x = D x D = | 15 3 13 3 | | 12 3 2 3 | = 45 39 36 6 = 84 42 = 2

Solve for y .

y = D y D = | 12 15 2 13 | | 12 3 2 3 | = 156 30 36 6 = 126 42 = −3

The solution is ( 2 , −3 ) .

Got questions? Get instant answers now!
Got questions? Get instant answers now!

Use Cramer’s Rule to solve the 2 × 2 system of equations.

   x + 2 y = −11 2 x + y = −13

( 3 , 7 )

Got questions? Get instant answers now!

Evaluating the determinant of a 3 × 3 matrix

Finding the determinant of a 2×2 matrix is straightforward, but finding the determinant of a 3×3 matrix is more complicated. One method is to augment the 3×3 matrix with a repetition of the first two columns, giving a 3×5 matrix. Then we calculate the sum of the products of entries down each of the three diagonals (upper left to lower right), and subtract the products of entries up each of the three diagonals (lower left to upper right). This is more easily understood with a visual and an example.

Find the determinant    of the 3×3 matrix.

A = [ a 1 b 1 c 1 a 2 b 2 c 2 a 3 b 3 c 3 ]
  1. Augment A with the first two columns.
    det ( A ) = | a 1 b 1 c 1 a 2 b 2 c 2 a 3 b 3 c 3 | a 1 a 2 a 3 b 1 b 2 b 3 |
  2. From upper left to lower right: Multiply the entries down the first diagonal. Add the result to the product of entries down the second diagonal. Add this result to the product of the entries down the third diagonal.
  3. From lower left to upper right: Subtract the product of entries up the first diagonal. From this result subtract the product of entries up the second diagonal. From this result, subtract the product of entries up the third diagonal.

Questions & Answers

In a triangle ABC prove that. (b+c)cosA+(c+a)cosB+(a+b)cisC=a+b+c.
Shivam Reply
give me the waec 2019 questions
Aaron Reply
the polar co-ordinate of the point (-1, -1)
Sumit Reply
prove the identites sin x ( 1+ tan x )+ cos x ( 1+ cot x )= sec x + cosec x
Rockstar Reply
tanh`(x-iy) =A+iB, find A and B
Pankaj Reply
B=Ai-itan(hx-hiy)
Rukmini
what is the addition of 101011 with 101010
Branded Reply
If those numbers are binary, it's 1010101. If they are base 10, it's 202021.
Jack
extra power 4 minus 5 x cube + 7 x square minus 5 x + 1 equal to zero
archana Reply
the gradient function of a curve is 2x+4 and the curve passes through point (1,4) find the equation of the curve
Kc Reply
1+cos²A/cos²A=2cosec²A-1
Ramesh Reply
test for convergence the series 1+x/2+2!/9x3
success Reply
a man walks up 200 meters along a straight road whose inclination is 30 degree.How high above the starting level is he?
Lhorren Reply
100 meters
Kuldeep
Find that number sum and product of all the divisors of 360
jancy Reply
answer
Ajith
exponential series
Naveen
what is subgroup
Purshotam Reply
Prove that: (2cos&+1)(2cos&-1)(2cos2&-1)=2cos4&+1
Macmillan Reply
e power cos hyperbolic (x+iy)
Vinay Reply
10y
Michael
Practice Key Terms 2

Get the best Algebra and trigonometry course in your pocket!





Source:  OpenStax, Algebra and trigonometry. OpenStax CNX. Nov 14, 2016 Download for free at https://legacy.cnx.org/content/col11758/1.6
Google Play and the Google Play logo are trademarks of Google Inc.

Notification Switch

Would you like to follow the 'Algebra and trigonometry' conversation and receive update notifications?

Ask